Methods and Challenges of Including Dust Evolution in Magnetohydrodynamic Simulations - Slavin, Jonathan D. (Journal of physics. Conference series, 2024)
Dust plays many important roles in the interstellar medium, affecting the heating, cooling and chemistry in all the different phases of the medium. Up until recently though, if dust was included in simulations at all, it was typically assumed that it was tightly coupled to the gas. More recent work has allowed for the dust to decouple from the gas, though this brings with it challenges for including all the dust destruction processes, especially grain-grain collisions. We discuss the various methods of simulating dust evolution in the context of magneto-hydrodynamical simulations of the interstellar medium and their strengths and weaknesses. In particular we present a method for improving on the tight coupling approach that shows promise for simulating the evolution of small grains subject to shocks.